Using archival information system for effective retrieval of document / Erindah Dimisyqiyani, Nissa Amandhea Wahyudjati and Amaliyah - Dimisyqiyani, Erindah; Wahyudjati, Amandhea; Amaliyah, Amaliyah (Universiti Teknologi MARA, Cawangan Melaka, 2022)
Archival have an important role in presenting information and evidence in an organization. Archival management who accurate can help archivists find the files they need. However, this is having not been implemented properly in the Plant Section of the PT Perkebunan Nusantara X Head Office which is uses a subject and area classification system. Archivists have difficulty finding the files they need, whether archival borrowed by employees or elsewhere, especially during the pandemic, there are employees who work with Work from Office and Work from Home systems. It is difficult for archivists to retrieve files borrowed by employees. This study uses qualitative research with a descriptive method through direct observation in the Plant section of the PT Perkebunan Nusantara X Head Office, interviews with archivists and literature studies. The results showed the ineffectiveness of the archive borrowing process at the Factory Section of the PT Perkebunan Nusantara X Head Office. This was due to the absence of procedure borrowing archive procedures, especially archive recording and loan history. In addition, archive management still uses a manual system. The archive classification system also does not follow the subject system, causing archivists to take longer to find archives when needed. The company has not determined the loan period and procedures for borrowing archives. In addition, there is no form for borrowing archives, so archivists have difficulty checking the history of borrowing archives. Based on the problems above, it can be concluded that the Plant Section of PT Perkebunan Nusantara X's Head Office needs an Archival Information System or Standard Operation Procedure for borrowing archives to minimize archive loss and improve archive management. With the archival information system can help archivists in managing archives, so that the performance of archivists in the Plant department becomes effective.